Determinan Perilaku Pengelolaan Keuangan Pada Generasi Z di Kota Pekanbaru - Septia, Leni; Nesneri, Yessi (Akuntansi dan Manajemen, 2024)
Financial management behavior is one of the issues that generation Z must pay attention to so that generation Z avoids excessive debt, can manage finances wisely, and is able to prepare themselves for a future with stronger financial stability. Because generation Z is an important group in Indonesian society and has great potential to shape the country's future. This research aims to determine the determinants of financial management behavior in Generation Z in Pekanbaru City through the variables of financial literacy, financial technology, lifestyle and parental income, with a sample of 270 respondents who were analyzed using the SEM-PLS 4.0 statistical tool. The results of the research show that the variables Financial Literacy, Financial Technology, Lifestyle have a positive and significant effect on Financial Management Behavior in Generation Z in Pekanbaru City, while the variable Parental Income does not have a significant effect on Financial Management Behavior in Generation Z in Pekanbaru City. The magnitude of the influence of Financial Literacy, Financial Technology, Lifestyle and Parental Income on Financial Management Behavior in Generation Z in Pekanbaru City is 61.1% and the remaining 38.9% is influenced by additional variables that were not studied.